Indonesian Younger Generation's Acceptance of Digital Da'wah - Usman, Usman; Siagian, Haidir Fitra (Jurnal Dakwah Risalah, 2024)
Digital media technology has a significant impact on life and using it for preaching (da’wah) is very important to expand the reach of the audience, including the younger generation. This study uses a descriptive qualitative approach. A Google Form containing 22 open-ended survey questions was distributed to various universities in four provinces in eastern Indonesia. A total of 29 survey responses were recorded, but only 9 responses could be analyzed using theory-based data triangulation techniques. Informants highlighted two main themes: appealing aspects of digital da'wah and challenges and criticisms of digital da'wah. The findings emphasize the need for digital da’wah that adds to religious insight and is engaging. It also found that the younger generation dislikes preachers who tend to justify their own group and discredit other groups.